Pengaruh Routing Adaptif OSPF terhadap Penggunaan Bandwidth pada Jaringan Komputer - Gozali, Ferrianto; Juniman, Juniman (Jurnal Teknik Elektro, 2003)
Routing protocol is a set of rules implemented by router in routing process to build a routingtable. The table is used as a reference to forward data packets from source to destination ininternetworks. There are three types of routing protocol: Distance vector, Link state andHybrid routing protocol. Open Shortest Path First (OSPF) is a Link state routing protocolthat implements SPF (Shortest Path First) Dijkstra algorithm to determine a shortest pathfrom source node to destination node. OSPF as a public domain routing protocol not onlyworks as an Interior Gateway Protocol (IGP) in certain Autonomous System (AS) but also asExterior Gateway Protocol (EGP) which able to control the route of data packets amongdifferent Autonomous Systems. This capability is achieved by implementing multipleinterfaces OSPF with separate topological databases with their own Links state informationin every Autonomous System. In this research, Zebra software package is used to implementOSPF routing protocol and for the purpose of analysis and measurement of the output weuse a linux web base packet-analyzer software package. The result we found indicates thatthe bigger number of router and link on the router, the bigger the bandwidth used innetworks while the bigger number of area, the smaller bandwidth used in every area.Keywords: OSPF, link state, routing protocol, autonomous system.